2017
DOI: 10.1115/1.4035368
|View full text |Cite
|
Sign up to set email alerts
|

On the Two-Dimensional Simplification of Three-Dimensional Cementless Hip Stem Numerical Models

Abstract: Three-dimensional (3D) finite element (FE) models are commonly used to analyze the mechanical behavior of the bone under different conditions (i.e., before and after arthroplasty). They can provide detailed information but they are numerically expensive and this limits their use in cases where large or numerous simulations are required. On the other hand, 2D models show less computational cost, but the precision of results depends on the approach used for the simplification. Two main questions arise: Are the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[ 47,132,135,143,144 ] Others consider either a frictionless contact [ 20,66 ] or a completely bounded specimen with no slipping allowed. [ 145 ] Lozanovski et al conducted a sensitivity analysis of three tangential frictional coefficients (0.3, 0.6, and 0.9) between the plate and lattice interface and found a negligible difference between the predicted Young modulus and the 0.2% yield stress. [ 132 ] Conversely, Galarreta et al showed that the modulus difference between a model with frictionless contact and a model with 0.2 and 0.3 frictional coefficient is 16.5% and 22.5%, respectively.…”
Section: Numerical Approachesmentioning
confidence: 99%
“…[ 47,132,135,143,144 ] Others consider either a frictionless contact [ 20,66 ] or a completely bounded specimen with no slipping allowed. [ 145 ] Lozanovski et al conducted a sensitivity analysis of three tangential frictional coefficients (0.3, 0.6, and 0.9) between the plate and lattice interface and found a negligible difference between the predicted Young modulus and the 0.2% yield stress. [ 132 ] Conversely, Galarreta et al showed that the modulus difference between a model with frictionless contact and a model with 0.2 and 0.3 frictional coefficient is 16.5% and 22.5%, respectively.…”
Section: Numerical Approachesmentioning
confidence: 99%